Effectiveness and safety of acupuncture and related therapies for pediatric asthma: a systematic review and meta-analysis - Wang, Jixuan; Fan, Shun; Su, Kaihan; Zhang, Jiacheng; Lu, Xuanjun; Guo, Shengxuan; Hu, Siyuan (Frontiers in Medicine, 2025)
ObjectivesThis study aims to investigate the efficacy and safety of acupuncture and related therapies as an adjunct to standard treatment (ST) in children with asthma.MethodsRandomized controlled trials (RCTs) comparing acupuncture combined with ST versus ST alone for pediatric asthma have been included. 8 databases and 3 clinical trial registries were searched, with the search completed up to January 31, 2025. The risk of bias in the included studies was assessed using the Risk of Bias 2 (RoB 2) tool. Data from the included studies were analyzed using R software version 4.4.2. The quality of evidence was evaluated using the Grades of Recommendations, Assessment, Development, and Evaluation (GRADE) approach.ResultsA total of 16 randomized controlled trials involving 1,675 participants have been included. Compared to ST, the addition of acupuncture has significantly improved the percent predicted values of forced expiratory volume in 1 second (FEV1pred%) [MD = 6.02, 95% CI (1.28, 10.76), p = 0.0128], No significant effect on forced expiratory volume in 1 second/forced vital capacity (FEV1/FVC) has been observed [MD = 3.36, 95% CI (−0.76, 7.48), p = 0.1097]. In addition, acupuncture has significantly reduced serum immunoglobulin E (IgE) levels [SMD = −0.88, 95% CI (−1.21, −0.55), p < 0.0001]. It has significantly increased serum immunoglobulin A (IgA) levels [MD = 0.31, 95% CI (0.22, 0.41), p < 0.0001]. It has also significantly improved serum immunoglobulin G (IgG) levels [MD = 1.71, 95% CI (1.39, 2.02), p < 0.0001]. Acupuncture has significantly increased peak expiratory flow (PEF) [MD = 3.15, 95% CI (1.16, 5.14), p = 0.0019]. It has significantly reduced serum interleukin-4 (IL-4) levels [SMD = −2.40, 95% CI (−2.75, −2.05), p < 0.0001]. Acupuncture has significantly decreased eosinophil (EOS) levels [MD = −1.06, 95% CI (−1.68, −0.43), p = 0.0010]. However, acupuncture has shown no significant effect on the pediatric asthma quality of life questionnaire (PAQLQ) scores [MD = 0.01, 95% CI (−0.39, 0.40), p = 0.9778].ConclusionAcupuncture has shown positive effects on certain serum immune and inflammatory biomarkers and FEV1 in pediatric asthma. It has not shown beneficial effects on FEV1/FVC. A substantial proportion of the evidence has been of low quality, and confidence in the results has been downgraded due to a serious risk of bias and inconsistency. The actual effects may differ substantially from the findings of this study. High-quality randomized controlled trials are still needed to confirm these findings in the future.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251039313.